(untitled) (Research, Society and Development, 2025)
Regular physical exercise promotes health, but can also play an important role in sustainability, when combined with awareness for environmental education. Objective to present an extension experience in the development of accessory prototypes for physical exercise, in the field of One Health. The methodology consisted of an experience report for the promotion of health and prevention of diseases, with teaching based on problems and environmental education. By means of waste and materials, a prototype was developed for use assisted by a qualified professional. It is possible to promote methodological diversity of learning, extensionist practices and allies in environmental awareness.